Pengaruh Fasilitas Infrastruktur Jalan Raya Di Desa Sumber Rejeki Terhadap Pertumbuhan Perekonomian Masyarakat - Ananda Hidayat; Tri Amar Prasetyo (Business and Enterpreneurship Journal (BEJ), 2023)
Infrastructure development is a government program in an effort to improve facilities and infrastructure. Where infrastructure development often raises pros and cons, as is the case with infrastructure development that occurs in villages of sources of fortune which give rise to many positive and negative sides. This study aims to determine the effect of infrastructure development on the people's economy in the Islamic economy. The research method used in this research is descriptive quantitative. The object of this research is the community around the construction project or the highway in Sumber Fortune village. The data sources used are primary data in the form of questionnaire results, observations and secondary data including documents from the village of the source of fortune which can be obtained through the official website belonging to the source of fortune. The analytical method used is simple linear regression analysis in the form of validity test, reliability test, t test, and coefficient of determination test. The results of the study show that infrastructure development has a significant impact on the community's economy. The development of new infrastructure is only limited to the form of government programs for the community, while the values of justice and responsibility in its implementation still need to be increased so that the infrastructure development program can be carried out effectively. Keywords: Infrastructure Development, Community Economic Condition